PROFIL MOTIVASI BELAJAR MAHASISWA CALON GURU KIMIA DAN KORELASINYA TERHADAP MODEL MENTAL (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2014)
The aim of this research was to know the learning motivation profile of the Pre-service Chemistry Teacher (PCT) from the first to the fourth grade. Besides that, the correlation between motivation and school chemistry mental model was also examined. The research was conducted using non experiment quantitative model, with the cross-sectional survey design and involved 124 PCT in Chemistry Education Department in one of universities in Bandung. The data was collected  from the Questionnaire of Motivation toward Chemistry Learning (QMCL) and the Diagnostic Test of School Chemistry Mental Models (DTSCM). The result of the descriptive analysis showed that the learning motivation of PCT was in the low category for the first grade (M=3,04; SD=0,24) and the middle category for the second (M=3,56; SD=0,20), the third (M=3,78; SD=0,26), and the fourth grade (M=3,89; SD=0,25). The result of Kruskal Wallis Test showed there was a significant difference in most of the learning motivations of PCT according to grades, except for achievement goals.  The learning motivaton of PCT moderately correlated with school chemistry mental model (r=0,399; p
Keywords: motivasi belajar; model mental; kimia sekolah; tes diagnostik; learning motivation; mental model; school chemistry; diagnostic test